Increase anti‐poaching law‐enforcement or reduce demand for wildlife products? A framework to guide strategic conservation investments. Issue 3 (2nd December 2018) - Holden, Matthew H.; Biggs, Duan; Brink, Henry; Bal, Payal; Rhodes, Jonathan; McDonald‐Madden, Eve
Abstract: Donors, NGOs, and governments increasingly invest in campaigns to reduce consumer demand for wildlife products in an attempt to prevent the decline of overexploited and poached species. We provide a novel framework to aid these investment decisions based on a demand reduction campaign's return on investment compared to antipoaching law enforcement. A resulting decision rule shows that the relative effectiveness of demand reduction compared to increased enforcement depends entirely on social and economic uncertainties rather than ecological ones. Illustrative case studies on bushmeat and ivory reveal that campaigning to reduce demand may be more cost‐effective than antipoaching enforcement if demand reduction campaigns drive modest price reductions. The outputs from this framework can link targeted monitoring of wildlife product prices to management decisions that protect species threatened by harvest and trade.